Lens density measurements by two independent psychophysical techniques. Issue 1 (December 2016) - Mukherjee, Anirbaan; Bone, Richard
Abstract Background Cataract, a leading cause of vision impairment, is due to the lens becoming excessively optically dense. Change in the lens optical density (LOD) could be a useful indicator of incipient nuclear cataract and would necessitate the development of accurate measurement techniques. Mapcat sf™ is a heterochromatic flicker photometer for measuring macular pigment optical density (MPOD) under photopic conditions. In the process, it also measures LOD that is needed in the calculation of MPOD. LOD is then converted by the instrument to "lens equivalent age" (LEA). However, varying cone photoreceptor ratios among individuals could affect the LEA measurement. Scotopic vision is mediated by rod photoreceptors; therefore, LEA measurement under scotopic conditions potentially provides a reliable standard for assessing other methods. The study was conducted to test the level of agreement between the LEA data obtained under photopic and scotopic conditions for a sample population. We also comment on factors that might contribute to any disagreement. Methods LEAs were obtained by Mapcat sf for 25 subjects and compared with those obtained under absolute scotopic threshold conditions. Results The mean scotopic LEA for the subjects was 2.7 years higher than the mean photopic LEA, but this difference was not statistically significant. Measurements by the two methods were reasonably correlated (r2 = 0.59, p < 0.0001). Significant individual differences in LEA by the two methods were found for six of the 25 subjects. Although our calculations included a standard long- to medium-wavelength-sensitive cone ratio, we found that different ratios could be found that rendered the differences in LEA insignificant for two of these six subjects. Variability in pupil diameter during scotopic measurements was considered another potential source of discrepancy between LEAs by the two methods. Conclusion The absolute threshold technique, with long adaptation times, is probably impractical for routine lens density measurement, whereas Mapcat sf provided a rapid, straightforward test that may find its application in optometric/ophthalmic practice.